Dispersal reduces interspecific competitiveness by spreading locally harmful traits. (16th August 2021) - Freedberg, Steven; Urban, Caroline; Cunniff, Brianna M.
Abstract: Just as intraorganismal selection can produce "selfish" elements that lower individual fitness, selection at the organismal level can favour traits that reduce the fitness of conspecifics and potentially impact population survival. Because dispersal can affect how these traits are distributed within species, it may determine whether their negative consequences are restricted locally or spread throughout the species' range. We present an individual‐based simulation model that explores the interaction between dispersal rate and traits that increase individual fecundity at the expense of conspecific fitness. We first modelled dispersal as a trait that varied within species and then fixed the within‐species dispersal rates and modelled competition between species that differed only in dispersal rate. Reproductive isolation allowed species differences in dispersal rates to become associated with traits moulded by intraspecific competition, but this association did not occur when dispersal variation was distributed within species due to recombination between the dispersal and competition loci. Alleles that reduced the fitness of conspecifics were maintained at lower frequencies in low‐dispersal species, resulting in a competitive advantage over high‐dispersing species. Although high‐dispersal species initially outcompeted low‐dispersal species owing to enhanced colonization opportunities, low‐dispersal species ultimately showed greater representation across a range of ecological and genetic scenarios. This process may shift the makeup of communities over time towards a greater representation of low‐dispersal species. Abstract : Intraspecific competition favours phenotypes that reduce conspecific fitness, increasing the risk of local extinction and colonization by interspecific competitors. Our individual‐based simulations show that high‐dispersal species are more prone to spread locallyharmful alleles among habitats, resulting in greater representation of low‐dispersal species.